Educational Practices and Challenges In Madrasas During The Late 19th And Early 20th Century Under The Turkestan General-Governorate - Xusniddin, Xolmatov (Pubmedia Social Sciences and Humanities, 2024)
This article analyzes the general state of madrasas in the Samarkand region, including their quantity and income, at the end of the 19th and the beginning of the 20th centuries. The exact number of students enrolled in these madrasas is provided based on historical sources. The study examines the geographical distribution of madrasas within the Samarkand region and explores the reasons for the disproportionate allocation of students among them. Additionally, the article provides detailed information about the learning process in the madrasas, including the academic subjects taught and the books used. An objective assessment is offered regarding the achievements and shortcomings of the educational process, as well as the quality of teaching materials. Furthermore, the study sheds light on the educational practices of Samarkand madrasas during this period, comparing them with those of madrasas in other regions.